ANALISIS FAKTOR MASALAH PERTUMBUHAN: STATUS GIZI, STUNTING PADA ANAK USIA < 5 TAHUN DI WILAYAH KERJA PUSKESMAS SIDOMULYO KOTA PEKANBARU - Wahyuni, Islah (Jurnal Kebidanan Mutiara Mahakam, 2020)
Background: The emergence of nutritional problems in toddlers is influenced by many interrelated factors. Directly influenced by some things, the toddler is not getting enough nutritious food balanced at the age of toddlers, the child does not get adequate nutritional care and children suffer from infectious diseases. Poverty is also one of the causes of malnutrition in regard to availability and consumption of family food. Less or worse nutritional problems and stunting are certainly required early detection attempts. Early detection of children's growth is an activity/examination to early find the existence of growth irregularities in infants The purpose of research: to do the growth factor: Nutrition Status, event Stunting in toddler aged < 5 years in the work area Puskesmas Sidomulyo Pekanbaru. Research method: The sample used in this research is a toddler in Sidomulyo Puskesmas work area which amounted to 30 toddlers 12-59 months with Consencutive sampling technique. The study took place in December 2019. Research instruments are digital weight scales, body length meters, Midline and questionnaires. Data analysis using the Rank Spearman. Research result: Classification of nutritional problems in infants based on the BB/U majority is BB less (underweight) 19 Reponden (63.3%). On a short (stunteed) majority, 14 respondents (46.7%), and based on the majority of the BB/TB of Good Nutrition (Normal) 17 respondents (56.7%). There are factors that affect the problem of nutritional status and stunting in children, from the knowledge aspect obtained by 16 respondents (53.3%) Less knowledgeable, the majority of maternal education was 19 (63.3%), there were a history of 23-person disease infections (76.7%), and a low family income of 20 people (66.7%) and incomplete immunizations as much as 17 people (56.7%). There is a relationship factor of mother knowledge with the problem of nutrition (stunting) (0.00), there is a relationship factor mother education with the problem of nutrition (stunting) (0.00), there is a relationship factor family income with nutrition (stunting) (0.001), there is a relationship factor of infection history in infants with stunting problems (0.00), there is a relationship factor immunization history with the problem of the nutrient (stunting) (0.010). It is expected that the health workers further improve the counseling and education to the toddler mother in monitoring nutritional problems and growth of toddlers